Prematurity, ventricular septal defect and dysmorphisms are independent predictors of pathogenic copy number variants: a retrospective study on array-CGH results and phenotypical features of 293 children with neurodevelopmental disorders and/or multiple congenital anomalies - I. Maini; I. Ivanovski; O. Djuric; S. G. Caraffi; E. Errichiello; M. Marinelli; F. Franchi; V. Bizzarri; S. Rosato; M. Pollazzon; C. Gelmini; M. Malacarne; et al. (BMC, 2018)
Abstract Background Since 2010, array-CGH (aCGH) has been the first-tier test in the diagnostic approach of children with neurodevelopmental disorders (NDD) or multiple congenital anomalies (MCA) of unknown origin. Its broad application led to the detection of numerous variants of uncertain clinical significance (VOUS). How to appropriately interpret aCGH results represents a challenge for the clinician. Method We present a retrospective study on 293 patients with age range 1 month - 29 years (median 7 years) with NDD and/or MCA and/or dysmorphisms, investigated through aCGH between 2005 and 2016. The aim of the study was to analyze clinical and molecular cytogenetic data in order to identify what elements could be useful to interpret unknown or poorly described aberrations. Comparison of phenotype and cytogenetic characteristics through univariate analysis and multivariate logistic regression was performed. Results Copy number variations (CNVs) with a frequency < 1% were detected in 225 patients of the total sample, while 68 patients presented only variants with higher frequency (heterozygous deletions or amplification) and were considered to have negative aCGH. Proved pathogenic CNVs were detected in 70 patients (20.6%). Delayed psychomotor development, intellectual disability, intrauterine growth retardation (IUGR), prematurity, congenital heart disease, cerebral malformations and dysmorphisms correlated to reported pathogenic CNVs. Prematurity, ventricular septal defect and dysmorphisms remained significant predictors of pathogenic CNVs in the multivariate logistic model whereas abnormal EEG and limb dysmorphisms were mainly detected in the group with likely pathogenic VOUS. A flow-chart regarding the care for patients with NDD and/or MCA and/or dysmorphisms and the interpretation of aCGH has been made on the basis of the data inferred from this study and literature. Conclusion Our work contributes to make the investigative process of CNVs more informative and suggests possible directions in aCGH interpretation and phenotype correlation.